Relation of vertical ground reaction forces while walking to contralateral structural worsening in adults with unilateral knee osteoarthritis: the Multicenter Osteoarthritis Study - Corrigan, Patrick; Lewis, Cara L.; Costello, Kerry E.; Kumar, Deepak; Felson, David T.; Neogi, Tuhina; Bacon, Kathryn L.; LaValley, Michael P.; Guermazi, Ali; Roemer, Frank; Nevitt, Michael C.; Lewis, Cora E.; et al. (Clinical biomechanics, 2026)
Background: It is unclear why knee osteoarthritis (KOA) progresses from a unilateral to bilateral joint disease. This study aimed to evaluate relations between vertical ground reaction forces (VGRFs) while walking and structural worsening in the unaffected limb of adults with unilateral KOA. Methods: Discrete metrics were extracted from the unaffected limb VGRF signal while walking at a self-selected speed. Structural worsening of the unaffected knee was evaluated over 2 years with radiographs (primary) and MRIs (secondary). Logistic regression models evaluated associations between VGRF metrics and structural worsening outcomes, while adjusting for relevant covariates. Similar relations were evaluated in adults without OA in either knee to determine if VGRF metrics uniquely relate to contralateral structural worsening in adults with unilateral KOA. Findings: In adults with unilateral KOA (n = 262), VGRFs were not associated with radiographic joint space narrowing within the tibiofemoral compartments of the unaffected knee. Additionally, VGRFs were not associated with MRI-detected cartilage loss in the medial tibiofemoral compartment. However, for the lateral tibiofemoral compartment, higher vertical loading and unloading rates were protective against cartilage loss (Odd ratios (OR) = 0.31–0.47), while larger vertical impulses and valley magnitudes were associated with increased odds of cartilage loss (OR = 2.50 and 2.26, respectively). No relations were found in adults without OA in either knee (n = 985). Interpretation: VGRF metrics lack the ability to predict medial tibiofemoral structural worsening in knees without OA. However, vertical impulse and valley magnitude can assist with identifying contralateral knees at risk for lateral tibiofemoral cartilage loss in those with unilateral KOA.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Biomechanics; Epidemiology; Gait; Musculoskeletal